Determinan Kinerja Sub Sektor Perikanan Guna Mendukung Ketahanan Ekonomi Di Provinsi Kepulauan Riau - Widiyarini Widiyarini; Said Latuconsina (Universitas Gadjah Mada, 2022)
ABSTRACT Riau Islands Province has a large potential of fishery resources but has not been utilized optimally to increase regional economic growth, in addition to the problem of territorial boundaries in the South Natuna Sea between Indonesia and Vietnam and China, as well as a decrease in the number of Indonesian fishing fleets operating in the province. The Riau Archipelago is faced with the proliferation of foreign fishing vessels looking for fish in the region. The purpose of this study is to find and analyze the effect of domestic investment, fishery business credit, fishery exports and the number of fishing fleets on the performance of the fisheries sub-sector in the Riau Islands Province. In this research, the natural logarithm equation (Ln) model is used, with explanatory research analysis research methods or hypothesis research through explanations of causal relationships between variables, while the research design uses panel data analysis cross section 7 cities/districts and time series for 6 years from 2015 to 2020 in the Riau Islands Province using quantitative inferential statistics. The result show that the variables of domestic investment, fishery business credit, fishery exports and the number of fishing fleets simultaneously have a significant effect, also partially have a significant and positive effect on the performance of the fisheries sub-sector in the Riau Islands Province. Likewise, the fishery sub-sector performance variable has a significant and positive